The effect of emotional information on Chinese word segmentation is influenced by word locations - Xiaoyang Zou; Bowen Xie; Wenjie Peng; Mengjie Ji; Die Qin; Jie Yuan (Acta Psychologica)
Chinese word segmentation is challenging due to the lack of clear word boundaries. This study investigated how emotional valence and word location affect Chinese word segmentation in vertical reading direction, using overlapping ambiguous strings (OAS). We conducted an online experiment (N = 193) and used generalized linear mixed-effects models (GLMM) for analysis. Results showed that in the upper-side condition, positive words were more easily segmented than negative and neutral words, indicating a positive advantage account. In the lower-side condition, emotional words were more easily segmented than neutral words, but no difference was found between positive and negative words, corresponding to the emotion advantage account. This study extends previous findings about emotion information and Chinese word segmentation to vertical reading direction. It reveals that the effect of emotion information on word segmentation is influenced by the specific location (dominant reading locations & subordinate reading locations) of emotional words, and is related to the spatial metaphor of words with different valences.